Transfer of 20,000 hectares of farmland to Fanaye: investment or grabbing and spoliations? - Aliou SENE (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
For a decade or more, Senegalese government action has been reflected in the gradual deployment of a policy of action oriented towards the intensification of agricultural products and the valorization of private entrepreneurship. It is in this context that the group consisting of Senhuile SA and Senethanol SA in agreement with the authorities of the country, in 2011, was trying to carry out a project of production of sunflower seeds and bioethanol on an area of 20 thousand hectares in the rural community of Fanaye (department of Podor, Saint-Louis region, at the level of the Senegal River Valley). Faced with this process of monopolization, the people of Fanaye, victims of the wickedness and sadism of these private companies to the great silence of the authorities, tried to resist against this fact accomplished. To curb, therefore, this allocation of peasant lands to private investors, several actions are carried out. Farmers use a repertoire of activities ranging from national and international press campaigns, to the filing of memoranda, to the organization of violent demonstrations and legal recourse. For example, peasants, shepherds, farmers, the unemployed, former illegal migrants, fishermen, herders whose survival is threatened (local grassroots groups and village women and youth committees) and Senegalese civil society organizations mobilized to stop these ruthless land grabbing of Fanaye lands, inherited from generation to generation. The stubbornness of the president of the rural council and the officials of the Senhuile SA and Senethanol SA company, as well as the deafening silence of the administrative authorities, despite the unceasing appeals of the population, led to violence resulting in loss of life and injuried people. This article describes and analyzes how the cession of 20,000 hectares of land to Italian investors, without any real consultation with the population, provoked an explosion of anger in the rural community of Fanaye, in the Senegal River Valley. The article aims to make the problem of land grabbing in Fanaye understood through abusive and illegal deliberations, to raise the impertinence, the opacity surrounding the Sénéthanol project, the economic and environmental risks, and the questionable approach of its leaders, as well as the various actions of the Collective in order to assert the right of the populations and to make peace reign.